2005
DOI: 10.1029/2004pa001048
|View full text |Cite
|
Sign up to set email alerts
|

Calcium isotope (δ44/40Ca) variations of Neogene planktonic foraminifera

Abstract: Measurements of the calcium isotopic composition (δ44/40Ca) of planktonic foraminifera from the western equatorial Pacific and the Indian sector of the Southern Ocean show variations of about 0.6‰ over the past 24 Myr. The stacked δ44/40Ca record of Globigerinoides trilobus and Globigerina bulloides indicates a minimum in δ44/40Casw (seawater calcium) at 15 to 16 Ma and a subsequent general increase toward the present, interrupted by a second minimum at 3 to 5 Ma. Applying a coupled calcium/carbon cycle model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 64 publications
4
80
0
Order By: Relevance
“…As a consequence, they are an important link between global calcium (Ca) and carbon (C) cycling. Because they act as a major Ca sink, coccoliths play an important role in determining the isotopic Ca budget of the marine realm, and consequently their isotopic composition is an important parameter for reconstructing the Ca budget of the global ocean (De La Rocha and DePaolo, 2000;Schmitt et al, 2003;Soudry et al, 2004;Heuser et al, 2005;Fantle and DePaolo, 2005). However, previous studies on coccolith oozes have reported a disparate range of seemingly conflicting Ca isotope values.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 81%
“…As a consequence, they are an important link between global calcium (Ca) and carbon (C) cycling. Because they act as a major Ca sink, coccoliths play an important role in determining the isotopic Ca budget of the marine realm, and consequently their isotopic composition is an important parameter for reconstructing the Ca budget of the global ocean (De La Rocha and DePaolo, 2000;Schmitt et al, 2003;Soudry et al, 2004;Heuser et al, 2005;Fantle and DePaolo, 2005). However, previous studies on coccolith oozes have reported a disparate range of seemingly conflicting Ca isotope values.…”
Section: A U T H O R ' S P E R S O N a L C O P Ymentioning
confidence: 81%
“…Negative values are set to 0-50 m. * δ 18 O Nps ratios from adjacent cores 23 277 and 23 254, see (Simstich et al, 2003). c Summer salinities and SSTs are averaged using depth corresponding hydrographic data from July-September (main planktonic bloom in the Nordic Seas (Kohfeld et al, 1996) variations of seawater Ca isotopic composition observed in the Early Pleistocene and Late Pliocene of ±0.2‰ compared to the modern seawater value (Fantle and DePaolo, 2005;Heuser et al, 2005;Sime et al, 2007) are within the analytical uncertainty and therefore negligible for the purpose of this study.…”
Section: Ca Isotope Analysismentioning
confidence: 99%
“…Most planktonic foraminifera species studied so far, dwelling in subpolar to subtropical temperate waters, exhibit a shallow slope for their temperature sensitivity (e.g. Gussone et al, 2003;Heuser et al, 2005;Sime et al, 2005Sime et al, , 2007Griffith et al, 2008). A detailed study on the temperature sensitivity of cultured Orbulina universa resulted in a temperature gradient one-order-of-magnitude smaller than that of N. pachyderma (sin.)…”
Section: Interspecies Comparison Of Core-topmentioning
confidence: 99%
“…This information is important as the chemical composition of the ocean itself is closely linked to the atmosphere and to the global climate. In order to reconstruct the calcium isotopic composition of the paleoocean archives such as brachiopods, belemnites, foraminifers, rudists, coccoliths, barites or phosphates are investigated (e.g., Nägler et al, 2000;Schmitt et al, 2003;Gussone et al, 2004;Fantle and DePaolo, 2005;Heuser et al, 2005;Immenhauser et al, 2005;Gussone et al, 2006;Hippler et al, 2006Hippler et al, , 2009Farkaš et al, 2007a,b;Sime et al, 2007;Griffith et al, 2008).…”
Section: Introductionmentioning
confidence: 99%